Polyandry in the Shadows: How Indonesian Judges Tackle Unregistered Marriages and Legal Uncertainty - Khairunnisa, Khairunnisa; Mahmud, Hafini Bin (Sakina: Journal of Family Studies, 2025)
Polyandry, where a woman is married to multiple men simultaneously, is explicitly prohibited under Indonesian marriage law and Islamic legal principles. This study examines how judges at the Banjarbaru Religious Court resolve polyandry cases resulting from extrajudicial divorce, with a focus on the legal implications from the standpoint of positive law. Employing an empirical juridical method with a qualitative approach, the research draws on primary data from semi-structured interviews with judicial officers. Findings indicate that judges address such cases by summoning relevant parties and evaluating evidence in accordance with Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). Judges view extrajudicial divorces as legally invalid, meaning the original marriage remains intact, and any subsequent marriage may result in de facto polyandry. Legally, such polyandrous marriages are annulled, and are treated as if they never existed. Consequently, any children born from these unions are only legally affiliated with the mother. This raises significant issues regarding paternal acknowledgment, inheritance, and other civil rights for the child. The study highlights how judges balance legal norms with sociological considerations, particularly the welfare of children. It further underscores the challenges arising from the public’s limited understanding of marriage registration requirements, which contributes to legal uncertainty and facilitates unrecognized marital arrangements. The research contributes to the discourse on marriage law enforcement in Indonesia and offers insight into judicial reasoning in complex family law cases involving polyandry, legal identity, and child welfare.